A Leguminous Tree New to the Flora of Assam - Sahni, K. C.; Dayal, R. (Indian Forester, 1970)
Ormosia glauca Wall., a tall tree from Garo Hills, Assam is reported for the first time from this floristically rich province. This rare species was known earlier from Nepal and Sivok Hills in Darjeeling District. Its possible modes of migration south-eastwards and measures for conservation are discussed.